The institutional context of an empirical law: the wage curve under different regimes of collective bargaining - Uwe Blien; Wolfgang Dauth; Thorsten Schank; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2009)
The wage curve identified by Blanchflower and Oswald (1994) postulates that the wage level is a decreasing function of the regional unemployment rate. In testing this hypothesis, most empirical studies have not taken into account that differences in the institutional framework may have an impact on the existence (or the slope) of a wage curve. Using a large-scale linked employer-employee data set for western Germany, this paper provides a first test of the relevance of different bargaining regimes and of works councils for the existence of a wage curve. In pooled regressions for the period 1998 to 2006 as well as in worker-level or plant-level fixed-effects estimations we obtain evidence for a wage curve for plants with a collective bargaining agreement at firm level. The point estimates for this group of plants are close to the -0.1 elasticity of wages with respect to unemployment postulated by Blanchflower and Oswald. In this regime, we also find that works councils dampen the adjustment of wages to the regional unemployment situation. In the other regimes of plants that either do not make use of collective contracts or apply sectoral agreements, we do not find a wage curve. – – Mit verbundenen Arbeitgeber-Arbeitnehmer-Daten für Westdeutschland wird in dieser Arbeit die Bedeutung von Tarifvertragsregimes und Betriebsräten für die Existenz einer Lohnkurve überprüft. Sowohl gepoolte Regressionen für 1998-2006 als auch Schätzungen mit fixen Effekten auf Ebene der Arbeitnehmer oder Betriebe deuten auf die Existenz einer Lohnkurve in der Gruppe der Betriebe mit Firmentarifvertrag hin (wobei hier überdies Betriebsräte die Lohnanpassung dämpfen). Die ermittelte Lohnelastizität bezüglich der regionalen Arbeitslosenquote liegt dabei in der Nähe des von Blanchflower und Oswald (1994) postulierten Wertes von -0,1. In anderen Regimes ohne Tarifvertrag oder mit Branchentarifvertrag finden wir dagegen keine Anzeichen für eine Lohnkurve.
Keywords: J50; 330; wages; wage curve; collective bargaining; Germany